Genetics and breeding of the ivory snail (Babylonia areolata): Current status, challenges and prospects - Vu, Van Sang; Thiyagarajan Vengatesen; Duc Long Nguyen; Vu, Thi Thao; Ngo, Thi Hoan; Le, Thi Nhu Phuong; Vu, Thi Thuy; Vu, Phuong Ha; Woo, Kim Hyun; Nguyen, Huy Hoang (Vietnam Journal of Biotechnology, 2026)
The ivory snail, Babylonia areolata, is a high-value marine mollusc widely distributed in the Indo-Pacific and increasingly farmed in Southeast Asia, particularly Vietnam. Its fast growth, short farming cycle, and strong market demand have made it a promising aquaculture species for the coastal provinces in Vietnam. However, the B. areolata industry faces major challenges, including low seed quality and poor broodstock management. To achieve sustainable and rapid development, the establishment of high-quality breeding populations for long-term improvement is essential. This review synthesizes current knowledge of reproductive biology, genetics and selective breeding for B. areolata, highlighting advances in molecular tools for assessing population structure, genetic variation, and trait-associated markers as well as prospects for a selective breeding program in Vietnam. Selective breeding programs targeting growth rate and disease resistance are discussed, alongside challenges such as the lack of comprehensive genomic resources, high larval mortality, and inbreeding risks. To meet the high-quality seed demand for ivory snail industry, a selective breeding program was initiated in Vietnam in 2024, focusing on improving growth rate. However, no genes or molecular markers have been identified for this species yet. By integrating modern genomic technologies with traditional selection approaches, B. areolata aquaculture can achieve significant genetic gains, ensuring the fast and sustainable development of strains that meet both commercial and conservation objectives.